Evaluación de los servicios del Centro Bibliográfico y Cultural de la ONCE: propuestas y alternativas. - Gutiérrez, Isabel (Revista General de Información y Documentación, 2001)
The article analyses the organizational structure and services affered by Cul tural Bibliographic Centre (CBC) of the Spain National Blind Organization (ONCE), so íhat the quality of services ané customer’s satisfaction will be evalua ted. The methode used is studyng service inside the organizational structure and processes, analysing the relationship between both. The conelutions are customer’s satisfaction is high, but the quality can be increased, giving ideas to succed it.